2005
DOI: 10.1124/mol.105.020701
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardic and Proarrhythmic Properties of Sinus Node Inhibitors

Abstract: Sinus node inhibitors reduce the heart rate presumably by blocking the pacemaker current I f in the cardiac conduction system. This pacemaker current is carried by four hyperpolarization-activated, cyclic nucleotide-gated cation (HCN) channels. We tested the potential subtype-specificity of the sinus node inhibitors cilobradine, ivabradine, and zatebradine using cloned HCN channels. All three substances blocked the slow inward current through human HCN1, HCN2, HCN3, and HCN4 channels. There was no subtype-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 30 publications
5
110
0
2
Order By: Relevance
“…Interestingly, all patients suffering from these mutations have in common that they display a more or less severe bradycardia, a clinical phenotype that is not observed in HCN channel-deficient mouse models. Another issue that is difficult to explain at this moment is the effect of bradycardic agents, such as cilobradine, ivabradine, and zatebradine (373), as well as of clonidine (208). It was proposed that these agents lower heart rate by blocking I h channels and reducing the firing frequency of SA node cells.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, all patients suffering from these mutations have in common that they display a more or less severe bradycardia, a clinical phenotype that is not observed in HCN channel-deficient mouse models. Another issue that is difficult to explain at this moment is the effect of bradycardic agents, such as cilobradine, ivabradine, and zatebradine (373), as well as of clonidine (208). It was proposed that these agents lower heart rate by blocking I h channels and reducing the firing frequency of SA node cells.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…Low micromolar concentrations of both blockers (IC 50 between 0.5 and 2 M) inhibit sinoatrial I h as well as heterologously expressed HCN channels in a use-dependent fashion (373,401). Like with ivabradine, zatebradine block results from drug molecules entering the channel pore from the intracellular site (115).…”
Section: A Heart Rate-reducing Agentsmentioning
confidence: 99%
“…Single myocytes from the sinus node were isolated and prepared for electrophysiological recordings as described previously (66,67). If was recorded with the whole-cell patchclamp recording in the presence or absence of 8-Br-cAMP.…”
Section: Methodsmentioning
confidence: 99%
“…The basis for association of a prolonged QTc with a decrease in HCN4 current amplitude is unclear, since a loss of function of If is not expected to prolong the QT interval, other than through a reduction in heart rate. Studies in both humans 34,35 and mice 36 have not observed prolongation of the QTc in response to If blockers.…”
Section: Hcn4mentioning
confidence: 99%